Lagotis brachystachya maxim attenuates chronic alcoholic liver injury combined with gouty arthritis in rats via its anti-inflammatory activity - Guo, Min-Xia; Zhang, Man-Man; Yang, Hai-Yan; Zhang, Chu-Ling; Cheng, Hong-Yu; Li, Na-Zhi; Yi, Li-Tao; Zhu, Ji-Xiao (Frontiers in Pharmacology, 2022)
Lagotis brachystachya Maxim, a common herb in Tibetan medicine, is mainly used to treat pneumonia, hepatitis, yellow water disease (gouty arthritis). Since long-term heavy drinking is also a risk factor for gouty arthritis, the present study aimed to evaluate the underlying protective role and mechanism of extracts of Lagotis brachystachya (ELB) in chronic alcoholic liver injury combined with gouty arthritis. The rat chronic alcoholic liver injury combined with gouty arthritis model was established by long-term alcohol consumption and monosodium urate (MSU) injection. The therapeutical action of ELB was then evaluated by biochemical measurement, histopathological examination, ankle swelling assessment, and protein detection. According to biochemical measurements and histopathological evaluation, ELB could alleviate the symptoms of alcoholic liver injury combined with gouty arthritis. In addition, chronic alcohol consumption and MSU activated inflammatory-related signaling such as TLR4/MyD88/NF-κB, NLRP3, and JAK2/STAT3 pathways in the liver and synovial tissues, while ELB significantly inhibited the activation of the inflammatory signaling pathway. In conclusion, ELB is protective in rats with chronic alcoholic liver injury and gouty arthritis, possibly mediated by the inhibition of TLR4/MyD88/NF-κB, NLRP3, and JAK2-STAT3 signaling pathways in both the hepatic and synovial tissues.